On the Evolution of the Mammalian Brain - Torday, John S.; Miller, William B. (Frontiers in Systems Neuroscience, 2016)
Hobson and Friston have hypothesized that the brain must actively dissipate heat in order to process information (Virtual reality and consciousness inference in dreaming. Front Psychol. 2014 Oct 9;5:1133.). This physiologic trait is functionally homologous with the first instantation of life formed by lipids suspended in water forming micelles- allowing the reduction in entropy (heat dissipation), circumventing the Second Law of Thermodynamics permitting the transfer of information between living entities, enabling them to perpetually glean information from the environment (= evolution). The next evolutionary milestone was the advent of cholesterol, embedded in the cell membranes of primordial eukaryotes, facilitating metabolism, oxygenation and locomotion, the triadic basis for vertebrate evolution. Lipids were key to homeostatic regulation of calcium, forming calcium channels. Cell membrane cholesterol also fostered metazoan evolution by forming lipid rafts for receptor-mediated cell-cell signaling, the origin of the endocrine system. The eukaryotic cell membrane exapted to all complex physiologic traits, including the lung and brain, which are molecularly homologous through the function of neuregulin, mediating both lung development and myelinization of neurons. That cooption later exapted as endothermy during the water-land transition (Torday JS. A Central Theory of Biology. Med Hypotheses. 2015 Jul;85(1):49-57), perhaps being the functional homolog for brain heat dissipation and consciousness/mind. The skin and brain similarly share molecular homologies through the ‘skin-brain’ hypothesis, giving insight to the cellular-molecular ‘arc’ of consciousness from its unicellular origins to integrated physiology. This perspective on the evolution of the central nervous system clarifies self-organization, reconciling thermodynamic and informational definitions of the underlying biophysical mechanisms, thereby elucidating relations between the predictive capabilities of the brain and self-organizational processes.